Establishment and traffic stress response of tall fescue as affected by Mycorrhiza fungi and Trinexapac-ethyl - Jabbari, Alireza; Rohollahi, Iman (Ornamental Horticulture, 2020)
Heavy traffic regularly causes damage of substantial aboveground parts to turf grasses. Several factors could affect the traffic stress severity, including the number of occasions per season and the soil moisture content during the traffic stress. Mycorrhiza results in numerous advantages to host plant like improving the turfgrass establishment, root structure and also abiotic stress tolerance of plants. Festuca arundinacea remains green during the playing season and it is the most popular turf grass for football. Trinexapacethyl (TE) might be influence the wear as growth retardant. Accordingly, mycorrhiza infection effect on tall fescue establishment, and TE effect on traffic stress after establishment were studied. The treatments, including traffic stress (traffic and non-traffic stress), TE (0 and 200 g 100 m-2) and mycorrhiza (Control; Glomus mosseae and Glomus intraradices) 50 g m-2 were evaluated on two cultivars of tall fescue in two growing season of 2017 and 2018. Both mycorrhizas were significantly colonized on turfgrass root during establishment. G. intraradices inoculation increased the establishment by passing 60 days from seeding in F. arundinacea cv. Barvado. After establishment, traffic stress reduced the relative water content (RWC) in 2017 and 2018, and also reduced the turf quality and soluble sugar content (SSC). TE improved the RWC, SSC, turf quality and also colonization percentage. Mycorrhiza inoculation enhanced tall fescue establishment. TE application at 200 g 100 m-2 had no influence on traffic stress, however, it improved turf quality, RWC, SSC and mycorrhiza colonization.